THE DEMOCRATIC MONARCHY POLITICAL ATTITUDES OF ARMY NON-COMMISSIONED OFFICER SCHOOL STUDENTS - Chaiyasit, Thawat; Thirasirikul, Jidapa; Chitlaoarporn, Chanchai (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The purposes of this study were: 1) to study the level of the democratic monarchy political attitudes of Army Non-Commissioned Officer School students; and 2) to study factors affecting the democratic monarchy political attitudes of Army Non-Commissioned Officer School students. The research was a quantitative study. The research instrument was a questionnaire. The sample group consisted of Army Non-Commissioned Officer School Students. Enrolling in the academic year 2022, number 400 people. The stats were Mean, Percentage, One Way ANOVA, and Pearson’s Moment Product Correlation. The research found: 1) The level of the democratic monarchy political attitudes of Army Non-Commissioned Officer School students was at a high level; 2) Peer group role, family role, and media role had a positive relationship on the level of the democratic monarchy political attitudes of Army Non-Commissioned Officer School students at the level of 0.05. As for the role of the friend group Role of educational institutions and the role of the media It affects political attitudes in a democratic monarchy political attitude. While the family role It has no effect on democratic monarchy political attitudes.